Development of a test rig to characterise magnetic bearing system - Wu, Vincent Shenmin. (2009)
Over the years, researchers have been trying to find a solution for heart failure patients and also those patients waiting for a heart transplant. These issues can be resolved by the implementation of ventricular assisted device (VAD) with the advent of technology and research. Since its development, VADs have undergone multiple technology changes from the first generation of pulsatile pump to the third generation magnetic-levitated continuous flow pump. As magnetic bearings are the key components in a typical third generation VAD, it is crucial to be able to analyse and characterise their properties. The main objective of this project is to develop a test rig to characterise magnetic bearing system. The project includes new design for the magnetic bearings and its driving motor. The new design of the hybrid magnetic bearings (HMB) system is more compact and smaller in size. The detailed steps of producing these hybrid magnetic bearings have been illustrated in the design procedure. Several pre-fabrication steps are involved in the project such as the set- up of the universal fixture assembly. The latter not only facilitates the coiling of copper wires to the desired amount, but also enables one to form shape for the motor coils. The hybrid magnetic bearing will be placed in specially designed test rigs where it undergoes some vibration tests to obtain its characteristics. Through the tests, the support parameters of the hybrid magnetic bearing system can be estimated. Therefore, a more efficient control system for the VADs can be developed.